Evolution of rapid blue‐light response linked to explosive diversification of ferns in angiosperm forests. Issue 3 (7th January 2021) - Cai, Shengguan; Huang, Yuqing; Chen, Fei; Zhang, Xin; Sessa, Emily; Zhao, Chenchen; Marchant, D. Blaine; Xue, Dawei; Chen, Guang; Dai, Fei; Leebens‐Mack, James H.; Zhang, Guoping; et al.
Summary: Ferns appear in the fossil record some 200 Myr before angiosperms. However, as angiosperm‐dominated forest canopies emerged in the Cretaceous period there was an explosive diversification of modern (leptosporangiate) ferns, which thrived in low, blue‐enhanced light beneath angiosperm canopies. A mechanistic explanation for this transformative event in the diversification of ferns has remained elusive. We used physiological assays, transcriptome analysis and evolutionary bioinformatics to investigate a potential connection between the evolution of enhanced stomatal sensitivity to blue light in modern ferns and the rise of angiosperm‐dominated forests in the geological record. We demonstrate that members of the largest subclade of leptosporangiate ferns, Polypodiales, have significantly faster stomatal response to blue light than more ancient fern lineages and a representative angiosperm. We link this higher sensitivity to levels of differentially expressed genes in blue‐light signaling, particularly in the cryptochrome (CRY) signaling pathway. Moreover, CRYs of the Polypodiales examined show gene duplication events between 212.9–196.9 and 164.4–151.8 Ma, when angiosperms were emerging, which are lacking in other major clades of extant land plants. These findings suggest that evolution of stomatal blue‐light sensitivity helped modern ferns exploit the shady habitat beneath angiosperm forest canopies, fueling their Cretaceous hyperdiversification. Abstract : See also the Commentary on this article by Chater, 230 : 886–888 .